Let's get physic(s)al!. (4th November 2021) - Borgongino, L; Rufrano Aliberti, S; Romeo, F; De Luca, R
Abstract: We present a kinematic model for horizontal, uphill, and downhill running by which simple expressions for power input and energy expenditure can be found. Total impulse as an estimator of the post-workout fatigue is also derived. The analysis, presented as a real-world application of kinematics, can be used as a monographic lecture for high school and first-year university physics students.